Submitted as a Partial Fulfillment of the Requirementsfor Getting Master Degree of Education in Educational Management Department - Sukamto, Sukamto (2011)
There are two objectives of this research. (1) To describe the characteristics of the structure and role of the new Students' recruitment at State-Owned Vocational School 2 Purbalingga. (2) To describe the criteria of the new students' recruitment at State-Owned Vocational School 2 Purbalingga. It is a qualitative research conducted in State-Owned Vocational School 2 Purbalingga. The main subject in this research included the principal, the chairman and members of the PPDB committee. Data collection techniques used in this research were observation, interview, and documentation. Data analysis technique used an analysis model, namely data collection, data reduction, data display, and conclusion. Data validity in this research included credibility, transferability, dependability, confirmability. The results of this research are (1) the new students' recruitment activity needs the committee structure to make it run well. The new students' recruitment committee is formed at least three months before the activity held. The school hold meeting that is attended by all staffs then chosen and form the committee. The structure of new students committee usually consists of the responsible person, chairman, secretary, treasurer, and sections. The role of each PPDB member has been regulated and divided based on the tasks in the Decree of the new students' recruitment committee. (2) The new students' recruitment process is started by the publication of the Principal's Decree on the Formation of the New Students' Recruitment (PPDB) Committee. Then, conduct a socialization that is followed by the registration process. The registration process is started by taking and filling out the form and submit it to the enrollment committee completed with the requirement documents. The next activity is the student candidates join the written test and interview. The new students' recruitment process at State-Owned Vocational School 2 Purbalingga still conducted manually or the students come directly to the school.